THE USE OF SCRABBLE FOR LEARNING ENGLISH VOCABULARY - Hapisoh; Riska Ramadhani (Perkumpulan Madani Publisher Indonesia, 2025)
Four language abilities that must be acquired are speaking, writing, listening, and reading. The language components of vocabulary, grammar, spelling, and pronunciation are among the talents. As one of the most important aspects of language comprehension, vocabulary can be enhanced through a variety of learning mediums. The goal of the study is to offer insightful information on the potential of Scrabble as an entertaining and dynamic method to support vocabulary development in a classroom context. This study uses a qualitative research design to examine how using Scrabble as a teaching tool might improve vocabulary mastery in Class X-1 students at SMAN 3 Panyabungan. This highlights the research's possible implications for teachers looking for creative ways to help secondary school pupils develop their language abilities while providing a peek into the methodology and expected results.